Um guia rápido sobre o desgaste dentário erosivo - Maltarollo, Thalya Horsth; Risemberg, Rabbith Ive Carolina Shitsuka; Pedron, Irineu Gregnanin; Martins, José Lucas; Shitsuka, Caleb; Friggi, Maria Naira Pereira (E-Acadêmica, 2022)
Erosive tooth wear (ETW) is considered an oral health problem, caused by chemical-physical processes resulting from repetitive exposure to acids (dental erosion) and physical forces (abrasion and attrition), which causes the loss of its mineral structure. This problem occurs in a multifactorial condition, and there may be an interaction between biological, dietary, behavioral and environmental factors. In recent years its prevalence has increased, making it a challenge for dentists, especially when it reaches more advanced stages where it can cause pain, hypersensitivity, problems with function and aesthetics. Through a literature review, the present study aims to present a brief guide on the etiology, diagnosis, prevention and treatments of ETW, helping the dentist in his clinical decision making. The dentist must carry out an early diagnosis and perform the appropriate treatment of this problem, being mainly dietary and oral hygiene guidelines in addition to fluoride therapies.